Impact of COVID-19 on Mental Health in Children and Adolescents. Issue 6 (November 2022) - Beal, Judy A.
Abstract : Recent research confirms the major negative effect the COVID-19 pandemic has had on the mental health of children and adolescents. Our pediatric nursing expert, Dr Beal, covers the latest evidence and summarizes several government reports on the pandemic's implications for youth mental health. Pediatric nurses are in a key position to identify youth who are experiencing these mental health issues and initiate timely referrals.